Perspectives on Microbial Electron Transfer Networks for Environmental Biotechnology - Zhou, Shaofeng; Song, Da; Gu, Ji-Dong; Yang, Yonggang; Xu, Meiying (Frontiers in Microbiology, 2022)
The overlap of microbiology and electrochemistry provides plenty of opportunities for a deeper understanding of the redox biogeochemical cycle of natural-abundant elements (like iron, nitrogen, and sulfur) on Earth. The electroactive microorganisms (EAMs) mediate electron flows outward the cytomembrane via diverse pathways like multiheme cytochromes, bridging an electronic connection between abiotic and biotic reactions. On an environmental level, decades of research on EAMs and the derived subject termed “electromicrobiology” provide a rich collection of multidisciplinary knowledge and establish various bioelectrochemical designs for the development of environmental biotechnology. Recent advances suggest that EAMs actually make greater differences on a larger scale, and the metabolism of microbial community and ecological interactions between microbes play a great role in bioremediation processes. In this perspective, we propose the concept of microbial electron transfer network (METN) that demonstrates the “species-to-species” interactions further and discuss several key questions ranging from cellular modification to microbiome construction. Future research directions including metabolic flux regulation and microbes–materials interactions are also highlighted to advance understanding of METN for the development of next-generation environmental biotechnology.